Forestry for sustainable rural development : (Ford Foundation, 1998)
This monograph uses community forestry as an all-encompassing operatioanl term. The common denominators in all community forestry programs are their focus on the rules of forest-dependent communities in managing resouces and sharing the benefits that flow from those resouce,..